Short-term and long-term effects of the enhance enforcement programmes on seatbelt wearing among front occupants in Malaysia - Norlen M; Mohammad-Fadhli M-Y; Ilhamah O; Noradrenalina I; Wahida A-B; Noor-Faradila P (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
To determine the effectiveness of the enhance enforcement programmes (The Ops) on the percentage of seatbelt wearing among front occupants in Malaysia. Methodology : The roadside observations for measuring the seatbelt wearing among front occupant were conducted before, two weeks and six months after the Ops. The study was conducted in selected states representing four different zones (Northern, Southern, Eastern and Central zones) of Peninsular Malaysia. Result : A total of 12,298 drivers and 11,212 front occupants were observed for their seatbelt wearing status through out the study. Percentage of seatbelt wearing among drivers and front passengers were increased from the baseline of 82.6 % and 74.4 % to 92 % (95 % CI: 91.2, 92.7) and 87.0 % (95 % CI: 85.9, 88.0) after two week, but declined to 85.7 % (95 % CI: 84.4, 86.8) and 76.8 % (95 % CI: 75.2, 78.3) after six months of the Ops respectively. Pre and post analysis revealed that after 2 weeks, the Ops were significantly effective in increasing the seatbelt wearing among front passengers and drivers with the RR (95 % CI) of 1.17 (1.14, 1.20) and 1.12 (1.10,1.13) respectively. However, after six months, the effectiveness of the Ops was reduced for both type of vehicle occupant. Conclusion : This study sheds light on the importance of the enhance enforcement programme for increasing the seatbelt wearing in Malaysia. However, in order to give more impact on seatbelt wearing, the strategy and the frequency of the enhance enforcement programme in Malaysia may need to be revised.